Cryogenic Freezing Equipment: a Review - S, Kumar (Journal of Postharvest Technology, 2013)
Innovative cryogenic freezing technologies can be used to  produce high quality frozen foods. The potential for the  development of new cryogenic equipment and processes is still  enormous. This paper presents the fundamentals of cryogenic  freezing and various food freezing technologies, discussing some  technical descriptions of representative freezing equipment  developed in the past. Product quality issues encountered when  using cryogenic systems with inappropriate knowledge of the  product or inadequate cold chain after cryogenic freezing -i.e.  recrystallization, mechanical damage and others- are also  addressed.
Keywords: Liquid nitrogen; Carbon dioxide; Food freezer,; Tunnel freezer; Rotary freezer